13‐Hydroxy‐9Z, 15Z‐Octadecadienoic Acid Production by Recombinant Cells Expressing Lactobacillus acidophilus 13‐Hydratase. (7th March 2016) - Kang, Woo‐Ri; Park, Chul‐Soon; Shin, Kyung‐Chul; Kim, Kyoung‐Rok; Oh, Deok‐Kun
Abstract: Recombinant Escherichia coli cells expressing linoleate 13‐hydratase from Lactobacillus acidophilus were permeabilized by treating with 0.2 M NaCl. The optimal conditions for the production of 13‐hydroxy‐9, 15( Z, Z )‐octadecadienoic acid (13‐HODE) from α ‐linolenic acid by permeabilized recombinant cells were pH 6.0, 40 °C, 7.5 % (v/v) methanol, 60 g/l permeabilized cells, and 15 g/l α ‐linolenic acid. Under these conditions, permeabilized cells produced 7.5 g/l 13‐HODE after 6 h, with a conversion yield of 50 % (w/w) and a volumetric productivity of 1.25 g/l/h. These values were 161 and 160 % of those obtained by nonpermeabilized cells, respectively. To the best of our knowledge, this is the first report on the process optimization for the biotechnological production of 13‐HODE.